ANALISIS KEUNTUNGAN PRODUK OLAHAN SUSU PASTEURISASI SKALA RUMAH TANGGA - Nastiti Winahyu; Retna Dewi Lestari (Universitas Duta Bangsa Surakarta, 2021)
Milk is a commodity that contains high protein and is healthy for the body. Public interest in milk consumption still needs to be increased by processing, especially pasteurized milk products. Processing can be done on a home industry scale and provides added value including product durability, taste variations, and selling prices. This study aims to determine the benefits obtained from processing pasteurized milk on a home industry scale. Product benefits are analyzed using the R/C ratio and Break Event Point. The results of the analysis show that home industry scale pasteurized milk is profitable and feasible. Product marketing is also supported by areas that are tourist sites. Therefore, in addition to increasing the added value of resilience and product variety, it is hoped that processing will also increase the income of local farmers.